The Impact of the Implementation of Regional Autonomy on the Quality of Public Services at the Population and Civil Registration Service of Palangka Raya City (2020-2024) - Mulyani, Sri; Rulandari, Novianita (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This study analyzes the impact of regional autonomy policies on the quality of public services at the Population and Civil Registration Service (Disdukcapil) of Palangka Raya City during the 2020-2024 period. The background of this study is related to the significant transformation in post-reform regional governance marked by regulatory changes and variations in the success of regional autonomy implementation across regions, affecting public service quality. Disdukcapil of Palangka Raya City, with a growing population of 293,457 people in 2023, faces challenges in providing quality services, with a public satisfaction index of 78.5% in 2023, still below the national target of 85%. The aim of this study is to analyze how regional autonomy implementation affects public service quality, identify factors influencing service quality, and provide recommendations for optimizing public services within the framework of regional autonomy. The research uses a qualitative approach with a literature review method, including analysis of policy documents, performance reports, academic journals, and official government publications. Data analysis employs qualitative content analysis with an interpretative analysis framework, including coding, categorization, and interpretation stages. The results show a significant increase in the Regional Government Implementation Index from 3.21 (2020) to 3.65 (2023), a digital transformation integrating 24 main public services, and increased service efficiency, marked by a reduction in service time from 45 minutes to 25 minutes and an increase in public satisfaction from 75.5% to 88.7%. The implications of this study make a significant contribution to developing an adaptive and sustainable public service model in the context of regional autonomy, with practical recommendations for strengthening human resource capacity, developing digital infrastructure, and improving inter-agency coordination.